LEADERSHIP IMPLEMENT IN SCHOOL ADMINISTRATION TOWARDS THE EFFICIENCY OF STUDENTS DEVELOPMENT OF VOCATIONAL STUDENTS AT THE HIGHER VOCATIONAL CERTIFICATE LEVEL - Pansuwan, Jarungrat; Utairat, Weerawat (Journal of MCU Nakhondhat, 2021)
The objectives of this research article were to study 1) The leadership of the vocational school director at the high vocational certificate level. 2) The school administrative to the efficiency of students development of vocational at the high vocational certificate level. 3) The leadership, which affects the school administrative to the efficiency of students development of vocational at the high vocational certificate level. The target group used in the research were 352 vocational school directors at the high vocational certificate level, 124 technical institutes, 139 professional college, 52 polytechnic college, and 37 vocational college. The instrument used in the research was a questionnaire. The first part was leadership of the vocational school director at the high vocational certificate level, the index of item objective congruence (IOC) was 0.9426, and Alpha coefficient was 0.973. The second part was school administrative to the efficiency of students development of vocational at the high vocational certificate level, the index of item objective congruence (IOC) was 0.9206, and Alpha coefficient was 0.987 The statistics for data analysis were the mean, standard deviation, and linear regression analysis. The results showed that 1) The leadership of the vocational school director at the high vocational certificate level were at the high level. 2) The school administrative to the efficiency of students development of vocational at the high vocational certificate level were at the high level. 3) The leadership, which affects the school administrative to the efficiency of students development of vocational at the high vocational certificate level, as shown in the equation : ( ) = .925 - .159(X1) + .127(X2) - .114(X14) + .207(X15) + .163(X16) + .168(X19)